The Influence of Liquidity and Profitability on Firm Value with Capital Structure as The Intervening (Study on Mining Sector Listed on IDX 2016-2020) - Fiqri, Nurul Izzah; Rokhmawati, Andewi; Rahmayanti, Elvi (JURNAL BISNIS STRATEGI, 2024)
This study aims to determine The Influence of Liquidity and Profitability on Firm Value with Capital Structure as The Intervening that study on the Mining Sector listed on IDX 2016-2020. The population used in this study were all mining sector companies listed on the Indonesia Stock Exchange (IDX) from 2016 to 2020. The population in this study were 52 mining sector companies conducted at the Indonesia Stock Exchange (IDX). The Indonesian Stock Exchange was determined as the research location by considering that the Indonesian Stock Exchange is one of the centres for selling shares of companies that go public in Indonesia. Secondary data which contains dependent and independent variables which were carried out in mining sub-sector manufacturing companies listed on the IDX for the period 2016 –  2020. In this study, the authors used a quantitative method with a descriptive and verification research approach. The technique of taking research samples using purposive sampling technique (8 companies). The results show that liquidity has a significant negative effect on firm value. profitabilityhas a significant negative effect on firm value, liquidity has a significant negative effect on capital structure, profitability has a significant negative effect on capital structure, capital structure has a significant positive effect on firm value, capital structure is unable to mediate the relationship between liquidity and firm value, capital structure is unable to mediate the relationship between profitability and firm value.